INCLUSIVE J-PRODUCTION IN Z(0) DECAYS - Adriani, O; Aguilarbenitez, M; Ahlen, S; Akbari, H; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; et al. (1992)
Inclusive J production in Z0 decays is observed via the leptonic decay mode J → ℓ+ℓ- (ℓ = e,μ). We measure the branching ratio Br(Z0 → J + X) = (4.1 ± 0.7 (stat.) ± 0.3 (sys.)) × 10-3. We have calculated the fraction of the J mesons from b-hadron decay and find a branching ratio of Br(b → J + X)= (1.3±0.2(stat.)±0.2(sys.)) × 10-2. We determine the average fractional energy of bottom hadrons 〈XE > = 0.70±0.03 (stat.)+0.02-0.01 (sys.) using the momentum spectrum of the J mesons. From a study of the angle between the J and the most energetic jet, we set an upper limit on the branching ratio Br(Z0 → qqg*;g* → J + X) < 7.0 × 10-4at 90% confidence level. © 1992.